PENJUALAN KERAMIK DENGAN CUSTOMER RELATIONSHIP MANAGEMENT BERBASIS WEB MOBILE PADA CV SARANA CIPTA GRAHA (Information Technology and Telematics, 2015)
Abstract CV  Sarana Cipta Graha is one of the distributors who is engaged in the sale of Roman ceramics, Niro and Halmar in Semarang. These ceramic supplies ordered directly from the factory to be sold in retail stores or party in Central Java. Every day this Graha Cipta Sarana CV accept orders from customers who want to buy ceramics by phone or come directly to the showroom.The objectives to be achieved is to make sales of ceramic with a web-based Customer Relationship Management Mobile on CV Cipta Graha Sarana which can increase sales of ceramics at Graha Cipta Sarana CV and can provide satisfactory services for customers Graha Cipta Sarana CV.The results in this study are ceramic with a CRM sales application CV Cipta Graha Sarana web-based mobile can deliver birthday greetings automatically if the customer's birthday, and giving discounts to customers when purchasing ceramic above certain purchases. Keyword : CV Sarana Cipta Graha, CRM, Web Mobile